KARAKTERISTIK PENGELOLAAN HUTAN RAKYAT DALAM PERSPEKTIF SISTEM (Studi di Desa Semoyo Kabupaten Gunung Kidul) - Tatik Suhartati; Ris Hadi Purwanto; Agus Setyarso; Sumardi Sumardi (Jurnal Hutan Tropis, 2021)
. Community smallholder forests in various places in Indonesia have different characteristics that depend on many factors that cause the development of community smallholder forests. This study aims to determine the characteristics of community smallholder forest management, the components and the interrelationships between the components that constructed the community smallholder forest system. The study was conducted at Semoyo Village, Gunungkidul Regency. Data were collected by interviewing seventy-two respondents who were purposively chosen, then tabulated and analyzed in a descriptive qualitative manner. Diameter of tree measurements on the respondent's forest land are carried out by census. In the next stage, the construction of the community smallholder forest system is carried out in a causal loop diagram based on the management characteristics found. The results show that the community smallholder forest system is composed of the main components of cultivated land, plant resources, human resources, management activities, and the purpose of managing forests. The component of land resources and human resources determines the agroforestry planting patterns chosen. The activity components, which are planting, maintaining, and cutting, have a positive loop and form different stand structures in different agroforestry planting patterns